Contributions to the issues of regional economic growth and equilibrium as well as the regional policy - György Kocziszky; József Benedek (Hungarian Geographical Bulletin, 2012)
The geopolitical change of direction taking place after 1989 induced a number of positive and negative social and economic changes in Hungary (as in the other post-socialist countries). Among the latter changes perhaps the most depressive one is that in the past two decades the economic policy has not been able to achieve a sustainable and balanced economic growth either in the short or in the long term, or to manage the problems arising from its lack. The external and internal imbalance (at macro and mezzo levels) arising in this way is continuously generating serious tensions. This paper wishes to find an answer to the question what role the regional policy can play in creating local and regional economic equilibrium and in starting a relative convergence.